(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Retailers are the most important link between manufacturers and consumers as it’s in their hands to sell the product. The retailer will only go for that company whose products not only are in demand but also which keep the retailers benefits in mind. Now day’s customers are very concerned and careful about the products they buy and want the best. Customer is the pivotal point in the marketing strategy of almost all the players The study involved the market survey of Union Territory- Sirsa, which is a major market of Vita products. The study is aimed at finding out the image of Vita, hold in this market and also to find out the retailers problem in the sale of Vita products. The aspect covered includes the kind of competition prevalent in the market, the growth of Vita and promotional practices to ensure quick movement of product from retail counters.